PEMBELAJARAN KETERAMPILAN BERBICARA DI SEKOLAH DASAR - Pandapotan Tambunan (JURNAL CURERE, 2018)
Learning speaking skills is an important material taught in schools. Because, through learning to speak students are expected to express/ convey thoughts, opinions, ideas, ideas, or feel well. However, speaking lessons have not been properly taught as the curriculum demands. Speech learning should be done through practice, not by presenting speech theories. To teach speech practice can be conveyed using the method of repeating the words, describing, answering questions, asking, digging questions, making pictures, telling stories, reporting, and role plying methods. To know the success of speaking learning can be done by carrying out the assessment. An assessment technique that can be used to assess students' speaking success is by reassigning according to what they want to assess.